Frequency and Determinant Factors for Calcification in Neurocysticercosis. (17th June 2020) - Bustos, Javier A; Arroyo, Gianfranco; Gilman, Robert H; Soto-Becerra, Percy; Gonzales, Isidro; Saavedra, Herbert; Pretell, E Javier; Nash, Theodore E; O'Neal, Seth E; Del Brutto, Oscar H; Gonzalez, Armando E; Garcia, Hector H; et al.
Abstract: Background: Neurocysticercosis is a major cause of acquired epilepsy. Larval cysts in the human brain eventually resolve and either disappear or leave a calcification that is associated with seizures. In this study, we assessed the proportion of calcification in parenchymal neurocysticercosis and risk factors associated with calcification. Methods: Data for 220 patients with parenchymal NCC from 3 trials of antiparasitic treatment were assessed to determine what proportion of the cysts that resolved 6 months after treatment ended up in a residual calcification at 1 year. Also, we evaluated the risk factors associated with calcification. Results: The overall proportion of calcification was 38% (188/497 cysts, from 147 patients). Predictors for calcification at the cyst level were cysts larger than 14 mm (risk ratio [RR], 1.34; 95% confidence interval [CI], 1.02–1.75) and cysts with edema at baseline (RR, 1.39; 95% CI, 1.05–1.85). At the patient level, having had more than 24 months with seizures (RR, 1.25; 95% CI, 1.08–1.46), mild antibody response (RR, 1.14; 95% CI, 1.002–1.27), increased dose albendazole regime (RR, 1.26; 95% CI, 1.14–1.39), lower doses of dexamethasone (RR, 1.36; 95% CI, 1.02–1.81), not receiving early antiparasitic retreatment (RR, 1.45; 95% CI, 1.08–1.93), or complete cure (RR, 1.48; 95% CI, 1.29–1.71) were associated with a increased risk of calcification. Conclusions: Approximately 38% of parenchymal cysts calcify after antiparasitic treatment. Some factors associated with calcification are modifiable and may be considered to decrease or avoid calcification, potentially decreasing the risk for seizure relapses. Abstract : We demonstrated residual calcification in 38% of viable parenchymal brain neurocysticercosis cysts that resolved after antiparasitic treatment. Combined antiparasitic therapy, early retreatment, and enhanced corticosteroid doses appear to reduce the risk of calcification and potentially reduce future seizure recurrence.